Differences in impact of official development assistance on foreign direct investment by aid types - Ono, Saori; Sekiyama, Takashi (Frontiers in Political Science, 2023)
While there have been studies on the impact of Official Development Assistance (ODA) on Foreign Direct Investment (FDI), few studies have examined the impact by aid type. Therefore, this study analyzed the impact by aid type using the Generalized Method of Moments with a gravity model for five major donor countries (France, Germany, Japan, the United Kingdom, and the United States) and 63 recipient country pairs from 1996 to 2020. Additionally, Granger causality tests, impulse response analyses and variance decomposition analyses using a panel vector autoregressive model were conducted to identify causal relationships in the time series and to quantitatively capture the impact. The estimation results suggest that Germany, Japan, and the United Kingdom's ODA Loans promote FDI. Their ODA Loans have a high proportion of economic infrastructure and productive-sector support. Hence, their ODA Loans may attract FDI to recipient countries by developing infrastructure in recipient countries such as transportation, telecommunications, energy, and finance.